2017
DOI: 10.5530/ijper.51.3s.55
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Phenolic Compounds from Oven and Microwave Dried Mushrooms (Agaricus bisporus and Pleurotus ostreatus) by Using Methanol, Ethanol and Aceton as Solvents

Abstract: Mushrooms can be native, less handled and readily present source of natural antioxidants. In this study, dried Agaricus bisporus and Pleurotus ostreatus were extracted with 80 % methanol, ethanol and acetone seperately. Total phenolics and antioxidant acitivities of extracts were determined by Folin-Ciocalteu method and DPPH and FRAP methods, respectively.The highest total phenolic contents were 31727 mg GAE (on d.b.), 33201 mg GAE (on d.b.) in methanolic extract of non-dried A. bisphorus and P. ostreatus resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The reduction of phenolic compounds during drying may be the result of the activation of oxidative enzymes (polyphenol oxidase and peroxidase) (An et al 2016) and the result of changes in the structure of the phenolic compounds (Toor and Savage 2006). Sezer et al (2017) did not find any relation between TP and drying temperate of mushrooms. Oven drying at 43°C did not affect TP or total flavonoid content in Pleurotus ostreatus (Mutukwa et al 2019).…”
Section: Resultsmentioning
confidence: 78%
“…The reduction of phenolic compounds during drying may be the result of the activation of oxidative enzymes (polyphenol oxidase and peroxidase) (An et al 2016) and the result of changes in the structure of the phenolic compounds (Toor and Savage 2006). Sezer et al (2017) did not find any relation between TP and drying temperate of mushrooms. Oven drying at 43°C did not affect TP or total flavonoid content in Pleurotus ostreatus (Mutukwa et al 2019).…”
Section: Resultsmentioning
confidence: 78%
“…It is important to note that the chemical composition of macrofungal biomass is strain-specific and strongly dependent on the environment and cultivation technique ( Bains et al., 2021 ). These days, numerous techniques can help in the extraction process, such as methanol extraction ( Sezer et al., 2017 ), enzyme assistance, microwave assistance, ultrasonic assistance, ethanol extraction ( Bae et al., 2015 ; Angelova et al., 2022 ), and hot water extraction ( Park and Hong, 2014 ). In this study, we used an 80% ethanol extraction method to extract pure phytochemicals and polysaccharides from MBE and BE.…”
Section: Resultsmentioning
confidence: 99%
“…The optimum percentage of MeOH in the solvent was the highest value within the range used in the study. Previous researches have confirmed that solvents with MeOH percentages over 98% or simply pure methanol achieve better yields of phenolic compounds and flavonoids from mushroom samples [50,51]. This is explained by the lower polarity of MeOH compared to that of water, which results in a higher affinity with the phenolic compounds.…”
Section: Total Phenolic Compounds Extractionmentioning
confidence: 85%